Double-Blinded, Vehicle-Controlled Proof of Concept Study to Investigate the Recurrence of Inflammatory and Noninflammatory Acne Lesions Using Tretinoin Gel (Microsphere) 0.04% in Male Patients after Oral Isotretinoin Use - Reid Vender; Ronald Vender (Hindawi Limited, 2012)
Background. Although isotretinoin orally is commonly used for moderate to severe or scarring acne, it is not a cure. Unfortunately recurrence is unpredictable and varies within the acne population. Objectives. Using a proof of concept study, determine the recurrence of acne after isotretinoin use in male patients. Methods. Twenty males aged 18-45 years old were enrolled. Subjects successfully completed a treatment of acne vulgaris with oral isotretinoin (120-150 mg/kg/course). Subjects were randomized 1 to 1. The study duration was 24 weeks. The primary endpoint measured was the absolute change in lesion counts from baseline to weeks 16 and 24. Local tolerability assessments were measured. Results. There were favorable changes in all outcomes measured. Overall, there was a 38.7% lower lesion count with tretinoin 0.04% microsphere gel use versus vehicle. The active product was well tolerated with great patient satisfaction. There were no significant safety issues. The limitations included the low number of patients enrolled, average age, and percentage of patients lost to follow-up. Conclusion. In summary, the results favored tretinoin 0.04% microsphere gel in the prevention of recurrent acne after isotretinoin use in male patients over 18 years old over a six-month period.